2014
DOI: 10.1016/j.bbamem.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the DGAT1 enzyme: Binding sites and substrate interactions

Abstract: Diacylglycerol acyltransferase 1 (DGAT1) is a microsomal membrane enzyme responsible for the final step in the synthesis of triacylglycerides. Although DGATs from a wide range of organisms have nearly identical sequences, there is little structural information available for these enzymes. The substrate binding sites of DGAT1 are predicted to be in its large luminal extramembranous loop and to include common motifs with acyl-CoA cholesterol acyltransferase enzymes and the diacylglycerol binding domain found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…Numerals indicate the locations of the different enzyme truncation points. S1 and S2 correspond to the acylCoA and diacylglycerol binding regions in the active site, respectively, which were identified in bovine DGAT1 (Lopes et al, 2014). The putative catalytic His (H), identified in murine DGAT1, also is shown in the topology (McFie et al, 2010).…”
Section: The Bnadgat1 N-terminal Domain Is Not Necessary For Catalysimentioning
confidence: 99%
See 1 more Smart Citation
“…Numerals indicate the locations of the different enzyme truncation points. S1 and S2 correspond to the acylCoA and diacylglycerol binding regions in the active site, respectively, which were identified in bovine DGAT1 (Lopes et al, 2014). The putative catalytic His (H), identified in murine DGAT1, also is shown in the topology (McFie et al, 2010).…”
Section: The Bnadgat1 N-terminal Domain Is Not Necessary For Catalysimentioning
confidence: 99%
“…That study also demonstrated the importance of the N-terminal region in forming dimers and tetramers and hypothesized the role of this region in enzyme regulation. The active site region in bovine DGAT1 was characterized through secondary structure analysis and binding studies of short peptide fragments spanning the predicted substrate binding sites (Lopes et al, 2014). The N and C termini of tung tree (Vernicia fordii) DGAT1 were both localized in the cytosol, and a C-terminal endoplasmic reticulum (ER) retrieval motif was shown to target the plant enzyme to the ER (Shockey et al, 2006).…”
mentioning
confidence: 99%
“…Substrate binding sites in bovine DGAT1 enzyme that are identical to portions of the ACAT and protein kinase C forms enzymes have been identified [17]. The diacylglycerol (DAG) binding site is located in a soluble extramembranenous loop of the protein, rather than in a transmembrane domain, suggesting it would interact with DAG headgroup on (or close to) the membrane surface [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The diacylglycerol (DAG) binding site is located in a soluble extramembranenous loop of the protein, rather than in a transmembrane domain, suggesting it would interact with DAG headgroup on (or close to) the membrane surface [17, 18]. Synthetic peptides (Sit1 and Sit2) corresponding to these proposed substrate binding sites of bovine DGAT1 [17] were shown to interact with the substrates for triacylglycerol synthesis (DAGs and acyl-CoAs) which are present in the membrane. Consequently, it is proposed that the peptides would need to interact with the membrane, in order to access and present the substrates to the catalytic histidine [19] which is located in the same extramembranous loop.…”
Section: Introductionmentioning
confidence: 99%
“…For DOG and OCoA in equal proportions at the interface, SIT2 cannot penetrate into the hydrophobic region, remaining in contact with the lipid polar head. For small proportions of OCoA in DOG or DOG in OCoA, Lopes et al[38] designed three peptides to investigate DGAT binding sites and substrate interactions: the first one, named Sit1, includes the most conserved region in DGAT1, the FYxDWWN segment. Sit2 is the putative diacylcgycerol binding domain, and includes the sequence HKWCIRHFYKP.…”
mentioning
confidence: 99%